Performance of engineered fibre reinforced concrete (EFRC) under different load regimes: A review. (1st November 2021) - Khalel, Hamad; Khan, Muhammad; Starr, Andrew; Khan, Kamran Ahmed; Muhammad, Asif
Highlights: Analysing the challenges related to mixing fibres in concrete mixture. Discussing the effects of fibres shapes and types on properties optimization. Highlighting the influence of fibre volume fraction on mechanical and fresh properties of concrete. Analysing the effectiveness of fibre reinforcement against coupled thermal and mechanical loads. Abstract: This review article presents a critical analysis by compiling the previous research studies with an emphasis on the optimization of fibre reinforced concrete to enhance its strength against different load regimes with a special focus on thermo-mechanical load conditions. The historical background, a description of the evolution of concrete as a material for advanced structures, and the fundamental principles of concrete production are provided as a preamble. Later, a discussion on FRC, fibre types and shapes, mixing methods and testing of properties is provided. A separate section describes how fibre mixing can affect fatigue and fracture behaviour, especially under different load regimes. Gaps in the existing research with possible new directions are discussed in the conclusion.